Income, social support networks, life satisfaction: Lesbians, gays, and bisexuals in Germany - Martin Kroh; Simon Kühne; Christian Kipp; David Richter (DIW Economic Bulletin, 2017)
Towards the very end of this legislative period, a cross-caucus parliamentary majority gave same-sex marriage the green light - progress for the legal equality of homosexuals in Germany. This report focuses on the life situations of homosexual and bisexual people in Germany. The careers they pursue, for example, differ from those of heterosexuals. Hourly wages are an area of significant disparity: homosexual and bisexual men earn less per hour than heterosexual men with the same qualifications in comparable professions. While differences in personality structure are virtually nonexistent, homosexuals and bisexuals describe themselves as less satisfied with their lives and under more psychological stress. An analysis based on the data from the Socio-Economic Panel (SOEP) at the German Institute for Economic Research yielded these and other results. The SOEP is one of the few representative population surveys in Germany that collects information on the sexual orientation of participants. Expanding the scope of regular social reporting to include data on sexual orientation would make it possible to better document differences in life situations and to more effectively identify where action is needed - such as in fighting discrimination.
Keywords: J7; J15; J16; 330; sexual orientation; LGB; partnerships; social support networks; education; labor market; earnings; satisfaction; health; personality; politicalattitudes